SPRAYING WITH AZOSPIRILLUM ON WHEAT LEAF AND NITROGEN COVERAGE RATES IN ITAPEVA-SP - Ferreira, J. P.; Nunes, R. F.; Silva, R. B.; Dal Bem, E. A.; Garcia, D. P.; Sabundjian, M. T.; de Souza, F. M. L. (Revista Brasileira de Engenharia de Biossistemas, 2017)
The use of diazotrophic bacteria in agriculture, especially in grasses, has the purpose of increasing the production and productivity allying with lower dose or suppression of the nitrogen sources applied for soil fertilization. Therefore, the objective of this work was to evaluate the viability of inoculation of Azospirillum brasilense via foliage with nitrogen doses in the production and yield of wheat. The experiment was carried out at Fazenda Bom Viver, Prestes Neighborhood in Itapeva, SP, in the 2016 harvest, and was carried out in no-tillage (SPC) in soybean and safrinha corn area. The treatments were in a 2x4 randomized block design (DBC) and the liquid formulation of Azospirillum brasiliense (AbV5 with 2x108 viable cells mL-1) was applied at a dose of 0,5 L. ha-1 foliar application and without application And subsequent nitrogen fertilization with 0; 30; 60 and 90 kg.ha-1 in coverage. Both the Azospirillum foliar application and the N coverage were applied after 30 days of sowing (30 DAS). The variety of wheat used in the planting was the Sinuelo, with management adopted by the owner of the area with application of growth regulator. The field evaluations of the plants were carried out, measuring: the height of the plants; Spikes per linear meter; Number of grains per spike; Hectoliter weight; Mass of a thousand grains and productivity. Due to the results obtained, there was higher plant height with increasing nitrogen doses in coverage. The inoculation of Azospirillum brasiliense via leaf did not show interaction between the doses of nitrogen in coverage, and there was no statistically increase in the components of wheat yield.